Mempromosikan Demokrasi yang Berkelanjutan di Sekolah-Sekolah Kamboja Melalui Pendidikan Kewarganegaraan dan Moral - Dock, Chanthoeurn; Perdana, Sukma Prasetya; Harmanto, Harmanto (Universitas Negeri Malang, 2023)
This study proposes the comprehensive implementation of civic and moral education programs and the impact of promoting sustainable democracy. This study uses qualitative research with a phenomenological approach. The subjects in this study focused on educators, high school students, and young people who were strategically selected through purposive sampling. Primary data sources were obtained through interviews, while secondary data sources were literature studies related to curriculum and school policies. The data collection technique uses in-depth interviews with a semi-structured format through open questions. The data obtained was translated and analyzed qualitatively. The results of the study show that comprehensive civic and moral education programs contribute to promoting democratic values and attitudes among youth. Instilling democratic values to increase youth participation and awareness in Cambodia requires steps including teacher training, curriculum changes, interactive learning, open political workings, and involving the community. Teaching better civic and moral education can help in maintaining democracy and the involvement of young people.